Rasional Instrumental dan Komersial Petani - Latang, Latang (Universitas Negeri Makassar, 2017)
The objective of this research is to improve the competence of farmers innovation and to commercially work. Specific targets to be achieved are analyzing the process of trying to improve people's welfare. The goal achievement method is to implement intensification, extensification, diversification, agricultural rehabilitation and cooperation with agricultural extension and to analyze the result of intstrumental rational action and commercial action. The results of this study describe the innovations developed by farmers and the innovations gained from agriculture. This research is conducted in Pallime Kabupaten Bone. The findings of this research can illustrate the techniques of innovating, intensifying and diversifying in order to produce export quality agricultural products. While other findings, farmers can increase the commercial competence of farming. Moreover, the results of research can be used as reference for the development of science and technology in the field of agriculture. This research can have implication to the improvement of people's prosperity which is in Pallime of Bone Regency. The conclusion of this research is farmer try farmer which suitable agriculture extension advocate and experience of farming. Farmers choose farming activities that can be commercially profitable from their rational actions. Farmers prioritize commercial benefits and optimal added value.